Polyelectrolyte-protein complexes structure and conformation of each specie revealed by SANS - Cousin, Fabrice (Langmuir : the ACS journal of surfaces and colloids, 2005)
We report here the structure of complexes made of proteins (lysozyme, positively charged) and polyelectrolytes (PSSNa, negatively charged). We stay in conditions where the volume fractions of the components are of the same order and where PSS concentrations correspond to a semidilute regime. The final complexes structure is determined by SANS. We obtain three main types of structures: (i) For a protein excess and for long polyelectrolyte chains, the network preformed by PSS chains still exists but chains are partially shrunk due to cross-linking by lysozyme. Macroscopically, samples are gelled. (ii) For a protein excess and for short polyelectrolyte chains, PSS chains are locally shrunk and do not form a network anymore. Lysozyme and PSS chains are embedded in dense 3-D aggregates that arrange in a fractal network at a larger scale. Macroscopically, samples are liquid. (iii) For a polyelectrolyte excess and whatever the chain length, the internal structure of the lysozyme changes. After an initial strong electrostatic binding, lysozyme is progressively unfolded thanks to a hydrophobic contact with PSS. The two chainlike objects are finally organized in a homogeneous costructure. Macroscopically, samples are liquids